A redefinition of Telagrion Selys and Aceratobasis Kennedy stat. rev. and the description of Schistolobos gen. nov. for Telagrion boliviense Daigle (Odonata: Coenagrionidae) - Von Ellenrieder, Natalia (2008)
The species currently included in Telagrion Selys are found to belong to three different genera: Telagrion sensu stricto, monotypic, including only the type species T. longum Selys, Schistolobos gen. nov., also monotypic, including Telagrion boliviense Daigle, and Aceratobasis Kennedy, resurrected to include Metaleptobasis cornicauda Calvert (type species), Agrion macilentum Rambur, Telagrion mourei Santos and T. nathaliae Lencioni. Synonymic lists, diagnoses, illustrations and distribution maps for the three genera and a key for species of Aceratobasis are provided.